Commuting as a factor in local public finance in Estonia.Pendelränne kui Eesti kohaliku omavalitsuse finantside mõjutaja. - Reiljan, Janno; Jaansoo, Annika (Estonian Discussions on Economic Policy, 2015)
Regions are increasingly competing indirectly because of the increasing mobility of populations. According to OECD (2005) figures, interregional commuting rates are high. Intraregional commuting rates are even higher and steadily increasing. Commuting has a significant influence on the income of municipal populations and so also tax revenues of local governments in Estonia, but this phenomenon has not yet been deeply studied. This paper aims to study the scope of commuting and the resulting effects relating to personal income tax on municipal budget revenues in Estonia, on the basis of data from the Estonian Tax and Custom Board. Based on the findings, it can be said that commuting is a very important factor in municipal development, as net income from commuting accounts for up to 80% of local government revenues from personal income tax.